MXene‐Integrated Responsive Hydrogel Microneedles for Oral Ulcers Healing - Chuanhui Song; Minhui Lu; Ning Li; Hongcheng Gu; Minli Li; Ling Lu; Yu Wang (Smart Medicine)
ABSTRACT Glucocorticoids such as dexamethasone have shown promising therapeutic effects in conquering oral ulcers. Challenges in this area are focused on enhancing the localized curative effects and responsive release. Herein, we presented a novel MXene‐integrated responsive hydrogel microneedle delivering dexamethasone to promote the healing of oral ulceration. By loading MXene, the hydrogel microneedles enable NIR (Near Infrared)‐responsive release of the inner dexamethasone for inflammation control and tissue regeneration. In addition, the MXene‐induced local hyperthermia could inhibit the bacteria, preventing the possible infection of ulcer lesions in the oral cavity. Based on these features, we demonstrated that our strategy could relieve local inflammation, promote tissue reconstruction, and accelerate wound healing in rat oral ulcer models. Overall, these NIR‐responsive MXene‐integrated hydrogel microneedles show significant promise in promoting ulcer healing and bring new ways for oral disease treatment.